2019
DOI: 10.5194/bg-2019-162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isotopic fractionation of carbon during uptake by phytoplankton across the South Atlantic subtropical convergence

Abstract: <p><strong>Abstract.</strong> The stable isotopic composition of particulate organic carbon (δ<sup>13</sup>C<sub>POC</sub>) in the surface waters of the global ocean can vary with the aqueous CO<sub>2</sub> concentration ([CO<sub>2(aq)</sub>]) and affects the trophic transfer of carbon isotopes in the marine food web. Other factors such as cell s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Such a reduction in the abundance of diatoms, a 13 C-rich carbon source in marine food webs (Fry & Wainright, 1991), is expected to decrease the δ 13 C values of consumers, and this diatom contribution has been emphasized in a recent model of phytoplankton δ 13 C variations in the global ocean (Magozzi et al, 2017). Tuerena et al (2019) also recently found that cell size was the primary determinant of δ 13 POC in the South Atlantic subtropical convergence zone and predicted that carbon isotopic fractionation will increase in the future, leading to lower δ 13 POC that may propagate through the food web. A decrease in the abundance of coccolithophores, another 13 C-rich carbon source, might also explain some of the tuna δ 13 C trend.…”
Section: Discussionmentioning
confidence: 99%
“…Such a reduction in the abundance of diatoms, a 13 C-rich carbon source in marine food webs (Fry & Wainright, 1991), is expected to decrease the δ 13 C values of consumers, and this diatom contribution has been emphasized in a recent model of phytoplankton δ 13 C variations in the global ocean (Magozzi et al, 2017). Tuerena et al (2019) also recently found that cell size was the primary determinant of δ 13 POC in the South Atlantic subtropical convergence zone and predicted that carbon isotopic fractionation will increase in the future, leading to lower δ 13 POC that may propagate through the food web. A decrease in the abundance of coccolithophores, another 13 C-rich carbon source, might also explain some of the tuna δ 13 C trend.…”
Section: Discussionmentioning
confidence: 99%